Artificial intelligence media-assisted storytelling therapy as a solution for handling speech delay in early childhood - Evi Chamalah; Azizah, Aida; Wulandari, Yosi; Wardani, Oktarina Puspita (Universitas Ahmad Dahlan, 2025)
This study investigates the effectiveness of Gemini AI-assisted storytelling therapy as an innovative approach to addressing speech delays in early childhood. Through qualitative methodology incorporating case studies, literature review, and action research with children aged 6-8 years, participants engaged in therapeutic storytelling sessions facilitated by Gemini AI, which generated personalized narratives based on individual abilities while providing real-time analysis of verbal responses. The AI system's adaptive algorithms continuously refined story content to match each child's developmental progress, creating an engaging learning environment throughout the intervention period. Sessions gradually increased linguistic complexity while incorporating children's preferences, fostering both communicative skills and emotional investment. Data collection included pre- and post-intervention assessments, recorded therapy sessions, parental interviews, and AI-generated progress reports tracking specific speech parameters. Results demonstrated significant improvements in vocabulary acquisition, sentence structure, and speaking confidence, with children exhibiting increased engagement during sessions while scheduling flexibility enhanced parental involvement. The findings confirm that AI-assisted storytelling therapy represents an effective intervention for speech delays, as the personalized content and real-time assessment capabilities complement traditional speech therapy approaches, potentially expanding accessibility to quality intervention while providing a scalable solution for the growing demand for specialized speech services.